M. Sordi, Storia politica del mondo greco, Milano, Vita e Pensiero, 1992 (19933), 426 pp. con 8 mapas + 18 fotografías (Minerva, 2019)
Review: M. Sordi, Storia politica del mondo greco, Milano, Vita e Pensiero, 1992 (19933), 426 pp. con 8 mapas + 18 fotografías